Management of acute intestinal failure: A position paper from the European Society for Clinical Nutrition and Metabolism (ESPEN) Special Interest Group. Issue 6 (December 2016) - Klek, Stanislaw; Forbes, Alastair; Gabe, Simon; Holst, Mette; Wanten, Geert; Irtun, Øivind; Damink, Steven Olde; Panisic-Sekeljic, Marina; Pelaez, Rosa Burgos; Pironi, Loris; Blaser, Annika Reintam; Rasmussen, Henrik Højgaard; et al.
Summary: Intestinal failure (IF) is the consequence of a reduction of gut function below the minimum necessary for the absorption of nutrients from the gastrointestinal tract. Types I and II comprise acute intestinal failure (AIF). Although its prevalence is relatively low, type II AIF is serious and requires specialist multidisciplinary care, often for prolonged periods before its resolution. The key aspects are: sepsis control, fluid and electrolyte resuscitation, optimization of nutritional status, wound care, appropriate surgery and active rehabilitation. The ESPEN Acute Intestinal Failure Special Interest Group (AIF SIG) has devised this position paper to provide a state-of-the-art overview of the management of type II AIF and to point out areas for future research.